Sustainability in the Face of Institutional Adversity: Market Turbulence, Network Embeddedness, and Innovative Orientation - Dirk De Clercq (2018)
© 2015, Springer Science+Business Media Dordrecht. Drawing from research on strategic choice, this study investigates the relationship between market turbulence and firms’ sustainable behavior, in the context of sustainability-related institutional adversity. It argues that the relationship between market turbulence and sustainability is mediated by network embeddedness, and this mediating role in turn is moderated by a firm’s innovative orientation. Data collected from a sample of Ontario restaurants inform predictions about firms’ propensity to adopt local wines in their portfolios, despite the limited market and normative support that these wines receive compared with imported wines. The study shows that market turbulence enhances sustainable firm behavior, through the development of strong network relationships. Furthermore, the mediating effect of network embeddedness is particularly salient among firms that exhibit a stronger innovative orientation. These findings reveal how and when turbulent market conditions can contribute to a firm’s sustainable behaviors in the presence of limited institutional support for such behaviors.